2021
DOI: 10.3390/antiox10111743
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Antioxidants in Age-Related Macular Degeneration and Glaucoma

Abstract: Age-related macular degeneration (AMD) and glaucoma are ophthalmic neurodegenerative diseases responsible for irreversible vision loss in the world population. Only a few therapies can be used to slow down the progression of these diseases and there are no available treatment strategies for reversing the degeneration of the neural retina. In AMD, the pathological process causes the malfunction and damage of the retinal pigmented epithelium and photoreceptors in the macula. In glaucoma, damage of the retinal ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 163 publications
0
30
0
Order By: Relevance
“…Dietary intake of carotenoids would be involved in modifying AGE accumulation in the body. The formation process of AGEs includes oxidative reactions [ 38 ]; therefore, the antioxidant effect of carotenoids suppressed these oxidation steps to reduce the production of AGEs accordingly [ 13 ]. This was supported by a report that administration of chestnut ( Tarpa bispinosa Roxb.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary intake of carotenoids would be involved in modifying AGE accumulation in the body. The formation process of AGEs includes oxidative reactions [ 38 ]; therefore, the antioxidant effect of carotenoids suppressed these oxidation steps to reduce the production of AGEs accordingly [ 13 ]. This was supported by a report that administration of chestnut ( Tarpa bispinosa Roxb.)…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants suppress inflammation caused by ROS and improve RGCs in experimental glaucoma [ 12 ]. Neurodegeneration caused by ROS is considered a modifiable factor of glaucoma onset and progression [ 13 , 14 ]. ROS is mainly generated by the metabolism of the mitochondria and neutralized by antioxidants [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that retinal degeneration can be induced by several factors, including genetic mutations, oxidative stress, and inflammation. Several treatments employing natural molecules, with antioxidant and/or anti-inflammatory actions, have shown efficacy in slowing the progression of retinal degeneration (e.g., AMD) [46].…”
Section: Phytonutrients As a Therapeutic Perspective In The Treatment...mentioning
confidence: 99%
“…ALA is a dithiol compound and functions as a cofactor of mitochondrial enzymes including pyruvate dehydrogenase and a‐ketoglutarate dehydrogenase, which are critical in fuel metabolism 14 . Meanwhile, ALA exerts anti‐oxidant actions owing to its dithiolane ring, 14–16 with the ability to quench free radicals and recycle other antioxidants, and therefore, it possesses beneficial effects on oxidative stress‐related diseases to some extent 17–20 . However, ALA in high dose interferes with the cellular redox state and suppresses cell growth 21–24 .…”
Section: Introductionmentioning
confidence: 99%
“…14 Meanwhile, ALA exerts anti-oxidant actions owing to its dithiolane ring, [14][15][16] with the ability to quench free radicals and recycle other antioxidants, and therefore, it possesses beneficial effects on oxidative stress-related diseases to some extent. [17][18][19][20] However, ALA in high dose interferes with the cellular redox state and suppresses cell growth. [21][22][23][24] It has been reported that ALA inhibits growth and induces apoptosis of various tumour cells including lung cancer cells, colorectal cancer cells, breast cancer cells, T-lymphoma cells and HepG2 hepatoma cells via the induction of oxidative stress and ER stress.…”
Section: Introductionmentioning
confidence: 99%